(untitled) (Information systems and technologies security, 2020)
One of the components of modern information systems is general-purpose computer equipment on which specialized software is installed or on which specialized software is working. This computer equipment requires a general-purpose operating system. To protect the information system it is necessary to protect all its links, including the operating system. In particular, in case of client-server technologies it is necessary to pay attention both to protection of server component and to protection of a client component. Protection of an operating system demands understanding, within what limits of what information system the OS will work, what working conditions and restrictions are imposed on the protected environment, what threats to the protected environment is required, what mechanisms is it possible to provide with protection of the environment necessary to us and what "price" of their application or nonapplication and other will be. Therefore, software safety should rely on a policy of safety of an operating system, expanding and specifying it and as much as possible. It is necessary to rely on safety mechanisms which are provided by an operating system or information system at software working out. This is necessary for unification and simplification of system of safety, simplification of its service, at the expense of reduction of quantity of the mechanisms created for the decision of the same problem. It is also necessary to apply typical and well-known components and standards, to avoid components with the closed source code as much as possible, or components which do not support, or incorrectly support typical standards. Obviously, incorrect protection of the operating system can lead to the failure of the security system as a whole, because the operation of specialized software and work with peripherals is under the control of the operating system. In article in detail offers concerning requirements to mechanisms of protection of operating systems are considered. These requirements are focused not on universal requirements, and consider various variants of use of computer devices.